PENGUASAAN PENGUKURAN VOLUME MELALUI PENDAMPINGAN PRAKTIKUM BERMEDIA BEAKER GLASS BRAILLE BAGI ANAK TUNANETRA - ROMDHON, ZAINAL (Jurnal Pendidikan Khusus, 2017)
Abstract: Practical learning method is one of the learning method that is very appropriate with the characteristic of learning of blind children. Especially in subjects that prioritize vision. Because  in practicum activities a blind child can identify with the rest of the senses they have. The purpose of this study is to describe the extent of the influence of media lab beaker glass mentoring toward mastery volume measurement braille for blind children in SMPLB-A YPAB Surabaya. This study used quantitative research methods, the design of Pre-Experimental Design with the kind of One-group pretest-posttest design. The subjects of this study as many as six children with visual impairments, data was collected using test techniques, Using the techniques of non-parametric statistical data analysis, according to the formula Wilcoxon Match Pair Test. The results showed the ability of blind children in the mastery of volume measurement tends to increase. It can be seen from the average value of 51.67 pretest and posttest score 88.33. While result of data analysis show that Ha> Ho. So it can be concluded Ha accepted, meaning there is influence Mastering Measurement Volume through Mentoring Beaker Glass Practicum mediated Braille for Blind Children in SMPLB-A YPAB Surabaya. Keywords: Volume Measurement, Practical Assistance